Electrolyte for metal-ion battery cells with high-capacity, micron-scale, volume-changing negative electrode particles

CN122968446APending Publication Date: 2026-10-23SHILLA NANOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611328350.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-09-11
Filing Date
2018-09-12
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

不幸的是,这样的颗粒相对较新,并且其在使用常规电解质的电池单元中的使用可能导致相对较差的电池单元性能特征和有限的循环稳定性

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968446A_ABST
    Figure CN122968446A_ABST
Patent Text Reader

Abstract

In one embodiment, a metal-ion battery cell includes a negative electrode, a positive electrode, a separator, and an electrolyte ionically coupling the negative electrode to the positive electrode. The negative electrode is a high-capacity electrode (e.g., in a range of about 2 mAh / cm 2 to about 10 mAh / cm 2 ). The electrolyte includes a solvent composition including a low-melting point (LMP) solvent in a range of about 10 vol% to about 80 vol% of the solvent composition and a regular-melting point (RMP) solvent in a range of about 20 vol% to about 90 vol% of the solvent composition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese invention patent application number "201880059341.2" entitled "Electrolyte for a metal-ion battery cell with high-capacity, micron-sized, volume-variable negative electrode particles".

[0002] Cross-reference to related applications

[0003] This patent application claims priority to U.S. Nonprovisional Application No. 16 / 128,340, filed September 11, 2018, entitled "Electrolyte for Metal-ion Battery Cells with High-Capacity, Micrometer-Scale, Volume-Change Anode Particles," and U.S. Provisional Application No. 62 / 557,416, filed September 12, 2017, entitled "Improved Liquid Electrolyte for Battery Cells with High-Capacity Anodes Based on Micrometer-Scale Volume Change Particles," both of which are expressly incorporated herein by reference in their entirety. Technical Field

[0004] This disclosure relates generally to energy storage devices, and more particularly to battery technology, etc. Background Technology

[0005] In part due to their relatively high energy density, relatively high specific energy, light weight and potential long lifespan, advanced rechargeable batteries are ideal for a wide range of consumer electronics devices, electric vehicles, grid storage and other important applications.

[0006] However, despite the increasing commercial adoption of these batteries, further development is needed, particularly for applications in low-emission or zero-emission, hybrid or all-electric vehicles, consumer electronics, wearable devices, energy-efficient cargo ships and locomotives, drones, aerospace applications, and power grids. In particular, further improvements are expected for a wide range of rechargeable batteries, such as rechargeable lithium and lithium-ion batteries, rechargeable sodium and sodium-ion batteries, rechargeable potassium and potassium-ion batteries, rechargeable calcium and calcium-ion batteries, and rechargeable magnesium and magnesium-ion batteries, to name just a few.

[0007] A wide range of electrolyte compositions can be used in the construction of lithium-ion and lithium-ion batteries, as well as other metal and metal-ion batteries. However, to improve battery cell performance (e.g., low and stable resistance, high cycle stability, high rate performance, etc.), it is necessary to develop the optimal choice of electrolyte for specific types and sizes of active particles in both the negative and positive electrodes, as well as for specific operating conditions (e.g., temperature, charging rate, discharging rate, voltage range, capacity utilization, etc.). In many cases, the choice of electrolyte components and their ratios is not unimportant and may even be counterintuitive.

[0008] In certain types of rechargeable batteries, charge storage anode materials can be formulated as high-capacity (nano) composite powders that exhibit moderately high volume changes (e.g., 8 vol% to 180 vol%) during the first charge-discharge cycle and moderate volume changes (e.g., 5 vol% to 50 vol%) during subsequent charge-discharge cycles. A subset of such charge storage anode particles includes anode particles with an average size (e.g., diameter or thickness) ranging from about 0.2 micrometers to about 40 micrometers. These types of charge storage particles offer promising prospects for scalable fabrication and achieving high cell-level energy densities and other performance characteristics. Unfortunately, such particles are relatively new, and their use in battery cells using conventional electrolytes can lead to relatively poor cell performance characteristics and limited cycle stability. When the capacity loading (area capacity) of the high-capacity (nano) composite anode becomes moderate (e.g., 2 mAh / cm²), the performance declines. 2 Up to 4mAh / cm 2 When the area capacity increases (e.g., 4mAh / cm²), the battery cell performance may become particularly poor, while when the area capacity increases (e.g., 4mAh / cm²), the battery cell performance may become particularly poor. 2 Up to 10mAh / cm 2 This is especially true when the electrode porosity (e.g., the volume occupied and filled by the electrolyte by the spacing between the (nano)composite active negative electrode particles in the electrode) becomes appropriately small (e.g., 25 vol% to 35 vol% after the first charge-discharge cycle), and this is even more true when the negative electrode porosity becomes smaller (e.g., 5 vol% to 25 vol% after the first charge-discharge cycle) or when the amount of binder and conductive additives in the electrode becomes appropriately small (e.g., 5 wt% to 15 wt%), and even more so when the amount of binder and conductive additives in the electrode becomes smaller (e.g., 0.5 wt% to 5 wt%). However, higher electrode density and lower binder and conductive additive content are beneficial for increasing battery cell energy density and reducing cost. Lower binder content may also be beneficial for improving battery cell rate performance.

[0009] Examples of materials exhibiting moderately high volume change (e.g., 8 vol% to 180 vol%) during the first charge-discharge cycle and moderate volume change (e.g., 5 vol% to 50 vol%) during subsequent charge-discharge cycles include (nano)composites, which include so-called conversion-type (including so-called chemical transformation and so-called “true transformation” subclasses) and so-called alloy-type active electrode materials. In the case of metal-ion batteries (such as Li-ion batteries), examples of such conversion-type active electrode materials include, but are not limited to, metal fluorides (such as lithium fluoride, iron fluoride, copper fluoride, bismuth fluoride, mixtures and alloys thereof), metal chlorides, metal iodides, metal bromides, metal chalcogenides (such as sulfides, including lithium sulfide and other metal sulfides), sulfur, selenium, metal oxides (including but not limited to lithium oxide and silicon oxide), metal nitrides, metal phosphides (including lithium phosphide), metal hydrides, etc. In the case of metal-ion batteries (such as Li-ion batteries), examples of such alloy electrode materials include, but are not limited to, silicon, germanium, antimony, aluminum, magnesium, zinc, gallium, arsenic, phosphorus, silver, cadmium, indium, tin, lead, bismuth, and their alloys. These materials typically exhibit higher gravimetric and volumetric capacities than the so-called intercalation electrodes commonly used in commercial metal-ion (e.g., Li-ion) batteries. Alloy electrode materials are particularly advantageous for use in certain high-capacity anodes of Li-ion batteries. Silicon-based alloy anodes may be particularly attractive for such applications.

[0010] Therefore, improvements are still needed in batteries, components, and other related materials and manufacturing processes. Summary of the Invention

[0011] The implementation scheme disclosed herein addresses the above requirements by providing improved batteries, components, and other related materials and manufacturing processes.

[0012] As an example, a metal-ion battery cell includes a negative electrode and a positive electrode, wherein the capacity load of the negative electrode is approximately 2 mAh / cm³. 2 Approximately 10mAh / cm 2The battery cell comprises negative electrode particles, wherein (i) the average particle size is in the range of about 0.2 micrometers to about 20 micrometers, (ii) the negative electrode particles exhibit volume expansion in the range of about 8 vol% to about 180 vol% during one or more charge-discharge cycles of the battery cell, and (iii) the negative electrode particles exhibit a specific capacity in the range of about 550 mAh / g to about 2200 mAh / g. The metal-ion battery cell further comprises: a separator electrically separating the negative electrode from the positive electrode, and an electrolyte ionically coupling the negative electrode to the positive electrode, wherein the electrolyte comprises one or more metal ion salts and a solvent composition. The solvent composition comprises: one or more low-melting-point solvents, the melting points of which are all in the range of about -140°C to about -60°C, and which are in the range of about 10 vol% to about 80 vol% of the solvent composition; and one or more conventional melting-point solvents, the melting points of which are all in the range of about -60°C to about +30°C, and which are in the range of about 20 vol% to about 90 vol% of the solvent composition. Attached Figure Description

[0013] The accompanying drawings are provided to help describe embodiments of this disclosure, and are intended to illustrate the embodiments only, not to limit them. Unless the context otherwise requires or implies, the shading, shading, and / or fill patterns in the drawings are merely for comparison between different components, elements, features, etc., and are not intended to express the use of particular materials, colors, or other properties that may be defined outside of this disclosure for particular patterns employed.

[0014] Figure 1 An exemplary Li-ion battery is shown in which the components, materials, methods, and other techniques described herein can be implemented.

[0015] Figure 2 Selected examples of suitable electrolyte components are shown.

[0016] Figures 3A to 3B Figures 4A to 4B, 5, 6, and 7A to 7C illustrate the effect of exemplary electrolyte compositions on the performance characteristics of a full cell having a (nano)composite negative electrode that exhibits high capacity, moderately high volume change during the first charge-discharge cycle, and moderate volume change during subsequent charge-discharge cycles. Detailed Implementation

[0017] Various aspects of the invention are disclosed in the following description and accompanying drawings of specific embodiments thereof. The term "embodiments of the invention" does not require that all embodiments of the invention include the discussed features, advantages, processes, or modes of operation, and alternative embodiments may be devised without departing from the scope of the invention. Furthermore, well-known elements of the invention may be omitted or not described in detail to avoid obscuring other more relevant details.

[0018] Any numerical range described herein with respect to any embodiment of the invention is intended not only to define the upper and lower limits of the relevant numerical range, but also to implicitly disclose each discrete value within the range whose unit or increment is consistent with the level of precision characterizing the upper and lower limits. For example, a numerical distance range of 7 nm to 20 nm (i.e., a level of precision in units of 1 or in increments of 1) includes a set of [7, 8, 9, 10, ..., 19, 20] (in nm), just as the intermediate numbers 8 to 19 in units of 1 or in increments of 1 are explicitly disclosed. In another example, a temperature range of about -120°C to about -60°C includes a set of temperature ranges of about -120°C to about -119°C, about -119°C to about -118°C, ... about -61°C to about -60°C (in °C), just as the intermediate numbers in the increment range between -120°C and -60°C (in °C) are explicitly disclosed. In yet another instance, the numerical percentage range of 30.92% to 47.44% (i.e., a level of precision in hundredths or increments of one hundredth) contains (in %) a set of [30.92, 30.93, 30.94, ..., 47.43, 47.44] as if intermediate numbers between 30.92 and 47.44 in hundredths or increments of one hundredths were explicitly disclosed. Therefore, it is intended that any intermediate numbers contained within any disclosed numerical range be interpreted as if such intermediate numbers had been explicitly disclosed, and any such intermediate number could thus constitute its own upper and / or lower bounds for subranges falling within a larger range. Therefore, it is intended that each subrange (e.g., each range including at least one intermediate number from the wider range as an upper and / or lower bound) be interpreted as implicitly disclosed by means of the explicit disclosure of the wider range.

[0019] While the following description may describe certain examples in the context of lithium (Li) and lithium (Li)-ion batteries (for brevity and convenience, and due to the current popularity of Li technology), it should be understood that many aspects are applicable to other rechargeable and primary batteries (such as Na-ion, Mg-ion, K-ion, Ca-ion, and other metal and metal-ion batteries, etc.). Furthermore, while the following description may also describe certain examples of material formulations in a Li-free state (e.g., in silicon-containing nanocomposite anodes), it should be understood that many aspects are applicable to Li-containing electrodes and active materials (e.g., partially or fully lithiated Si-containing anodes, partially or fully lithiated metal fluoride-containing cathodes (such as mixtures of LiF and metals, such as Cu, Fe, Cu-Fe alloys, various other alloys, and metal mixtures, etc.), partially or fully lithiated chalcogenides (such as Li₂S, Li₂S / metal mixtures, Li₂Se, Li₂Se / metal mixtures, Li₂S-Li₂Se mixtures, various other compositions containing lithiated chalcogenides, etc.), partially or fully lithiated metal oxides (such as Li₂O, Li₂O / metal mixtures, etc.), and so on.

[0020] Furthermore, while the following description may describe certain examples within the context of specific alloying and conversion chemistry of the anode and cathode active materials in Li-ion batteries (such as silicon-containing anodes or metal fluoride-containing or lithium sulfide-containing cathodes), it should be understood that many aspects are applicable to other chemistry of Li-ion batteries (other conversion and alloying electrodes and various intercalation electrodes) and other battery chemistry. In the case of metal-ion batteries (such as Li-ion batteries), examples of other suitable conversion electrodes include, but are not limited to, metal chlorides, metal iodides, metal bromides, sulfur, selenium, metal oxides, metal nitrides, metal phosphides, metal hydrides, etc.

[0021] During battery operation (such as a Li-ion battery), the conversion material changes (converts) from one crystal structure to another (hence the term "conversion"). This process also involves breaking chemical bonds and forming new ones. In the case of a Li-ion battery, Li ions are inserted into an alloy-type material during operation to form a lithium alloy (hence the term "alloy"). Sometimes, "alloy" type electrode materials are considered a subclass of "conversion" type electrode materials.

[0022] Figure 1An exemplary metal-ion (e.g., Li-ion) battery is illustrated, wherein the components, materials, methods, and other technologies or combinations thereof described herein may be applied according to various embodiments. A cylindrical battery is shown herein for illustrative purposes, but other types of arrangements, including prismatic or pouch-shaped (laminated) batteries, may be used as needed. The exemplary battery 100 includes a negative electrode 102, a positive electrode 103, a separator 104 inserted between the negative electrode 102 and the positive electrode 103, an electrolyte (implicitly shown) impregnated with the separator 104, a battery casing 105, and a seal 106 sealing the battery casing 105.

[0023] The conventional electrolyte for this type of Li-based or Na-based battery typically consists of a 0.8 M to 1.2 M (1 M ± 0.2 M) solution of a single Li or Na salt (such as LiPF6 for Li-ion batteries and NaPF6 or NaClO4 salts for Na-ion batteries) in a mixture of a carbonate solvent and 1 wt% to 2 wt% of other organic additives. Common organic additives may include nitriles, esters, sulfones, sulfoxides, phosphorus-based solvents, silicon-based solvents, ethers, etc. Such additive solvents can be modified (e.g., sulfonated or fluorinated).

[0024] The most common salt used in most conventional Li-ion battery electrolytes is LiPF6. Examples of less common salts (e.g., those primarily discussed in research publications, or in some cases never even described in Li-ion battery electrolyte applications, but still potentially applicable and useful) include: lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroantimonyate (LiSbF6), lithium hexafluorosilicate (Li2SiF6), lithium hexafluoroaluminate (Li3AlF6), lithium bis(oxalate)borate (LiB(C2O4)2), lithium difluoro(oxalate)borate (LiBF2(C2O4)), and various lithium imides (such as SO2FN). − (Li + SO2F, CF3SO2N − (Li + SO2CF3, CF3CF2SO2N − (Li + SO2CF3, CF3CF2SO2N − (Li + SO2CF2CF3、CF3SO2N − (Li + SO2CF2OCF3, CF3OCF2SO2N − (Li + SO2CF2OCF3, C6F5SO2N − (Li + SO2CF3, C6F5SO2N− (Li + SO2C6F5 or CF3SO2N − (Li + SO2PhCF3, etc.

[0025] Electrodes used in Li-ion batteries are typically manufactured by: (i) forming a slurry containing active materials, conductive additives, a binder solution, and in some cases, surfactants or other functional additives; (ii) casting the slurry onto a metal foil (e.g., Cu foil for most negative electrodes and Al foil for most positive electrodes); and (iii) drying the cast electrode to completely evaporate the solvent.

[0026] The conventional negative electrode materials used in Li-ion batteries are intercalation-type. During the charging or discharging process, metal ions intercalate and occupy interstitial sites in such materials. When used in electrodes, such negative electrodes undergo small or very small volume changes. Polyvinylidene fluoride (PVDF) and carboxymethyl cellulose (CMC) are two of the most common binders used in these electrodes. Carbon black is the most commonly used conductive additive in these electrodes. However, such negative electrodes exhibit relatively small gravimetric and volumetric capacities (typically less than 370 mAh / g rechargeable specific capacity in the case of graphite or hard carbon-based negative electrodes, and less than 600 mAh / cm² at the electrode level, without considering the volume of the current collector foil). 3 (Rechargeable volumetric capacity).

[0027] Compared to intercalation-type anodes, alloy anode materials for Li-ion batteries offer higher gravimetric and volumetric capacities. For example, silicon (Si) offers approximately 10 times the gravimetric capacity and approximately 3 times the volumetric capacity compared to intercalation-type graphite (or graphite-like) anodes. However, Si suffers significant volume expansion (up to approximately 300 vol%) during Li insertion, which can lead to thickness variations and mechanical failures in Si-containing anodes. Furthermore, Si (and some Li-Si alloy compounds that may form during Si lithiation) exhibits relatively low electrical conductivity and relatively low ionic (Li-ion) conductivity. The electronic and ionic conductivity of Si is lower than that of graphite. The formation of (nano)composites containing Si particles (including but not limited to Si-carbon composites, Si-metal composites, Si-polymer composites, Si-ceramic composites, composites containing nanostructured Si, carbon, polymers, ceramics and metals, or other types of porous composites containing nanostructured Si or nanostructured or nano-sized Si particles of various shapes and forms) can reduce volume changes during Li ion insertion and extraction, which in turn can lead to better cycle stability of rechargeable Li-ion battery cells.

[0028] Besides Si-containing nanocomposite anodes, other examples of such nanocomposite anodes containing alloy-type active materials include, but are not limited to, those containing germanium, antimony, aluminum, magnesium, zinc, gallium, arsenic, phosphorus, silver, cadmium, indium, tin, lead, bismuth, and their alloys.

[0029] Besides (nano)composite anodes containing alloy-type active materials, other types of high-capacity (nano)composite anodes of interest may include metal oxides (including silicon oxide, lithium oxide, etc.), metal nitrides, metal phosphides (including lithium phosphide), metal hydrides, etc.

[0030] In particular, high-capacity (nano) composite anode powders are especially attractive for battery applications in terms of manufacturability and performance characteristics. These powders exhibit a moderately high volume change during the first charge-discharge cycle (e.g., about 8 vol% to about 180 vol%), a moderate volume change during subsequent charge-discharge cycles (e.g., about 4 vol% to about 50 vol%), and an average size in the range of about 0.2 μm to about 40 μm (more preferably about 0.4 μm to about 20 μm for some applications). The electrode area capacity loading is moderate (e.g., about 2 mAh / cm²). 2 Approximately 4mAh / cm 2 ) to high (e.g., about 4mAh / cm) 2 Approximately 10mAh / cm 2 Electrodes containing nanocomposite anode materials are particularly attractive for use in battery cells. In some designs, the near-spherical (globose) shape of these composite particles can be additionally attractive for increasing the rate performance and volumetric capacity of the electrode. While some improvements can be achieved by forming and utilizing one or more alloying or conversion-type active materials containing such nanocomposite anode materials, as well as electrode formulations, significant additional improvements in battery cell performance characteristics can be achieved by improving the composition and preparation of the electrolyte (e.g., liquid electrolyte), beyond what is known or shown by conventional prior art. Unfortunately, high-capacity (nanocomposite) anode and cathode powders are relatively new, and their performance characteristics and limited cycle stability are generally relatively poor, especially if the electrode areal capacity loading is moderate (e.g., about 2 mAh / cm²). 2 Approximately 4mAh / cm 2 And if the electrode area capacity loading is high (e.g., about 4 mAh / cm²), 2 Approximately 10mAh / cm 2This is even more true for high-capacity (nano) composite anode and cathode powders, which exhibit moderately high volume changes during the first charge-discharge cycle (e.g., about 8 vol% to about 180 vol%) and moderate volume changes during subsequent charge-discharge cycles (e.g., about 4 vol% to about 50 vol%), with average sizes ranging from about 0.2 micrometers to about 40 micrometers and relatively low densities (e.g., about 0.5 g / cc to 3.8 g / cc). However, the higher capacity loading is beneficial for increasing the energy density of the battery cell and reducing the manufacturing cost of the battery cell. Similarly, cell performance can be affected when the porosity of such electrodes (e.g., negative electrodes)—the volume occupied and filled with electrolyte by the spacing between (nano)composite active negative electrode particles in the electrode—becomes appropriately small (e.g., from about 25 vol% to about 35 vol%), and even more so when it becomes small (e.g., from about 5 vol% to about 25 vol%); or when the amount of binder and conductive additives in the electrode becomes appropriately small (e.g., from about 6 wt% to about 15 wt% in total), and even more so when it becomes small (e.g., from about 0.5 wt% to about 5 wt% in total). However, in some applications, higher electrode density and lower binder content are beneficial for increasing cell energy density and reducing cost. Lower binder content also benefits cell rate performance. Larger volume variations lead to poorer performance in some designs, which may be related to damage to the solid electrolyte interphase (SEI) layer formed on the negative electrode, uneven lithiation and delithiation of electrode particles within the electrode, and other factors.

[0031] Surprisingly, the inventors have discovered that electrolyte compositions (with a variety of particle sizes) that perform well for intercalated negative and positive electrodes, as well as for nanoscale (e.g., in the range of about 1 nm to about 200 nm) conversion negative and positive electrode materials or nanoscale (typically in the range of 1 nm to 200 nm) alloy negative electrode materials, perform poorly in battery cells containing high-capacity (nano) composite negative electrode particles (e.g., powder) that exhibit a reasonably high volume change (e.g., about 8 vol% to about 180 vol%) during the first charge-discharge cycle, a moderate volume change (e.g., about 4 vol% to about 50 vol%) during subsequent charge-discharge cycles, and an average size in the range of about 0.2 micrometers to about 40 micrometers. Furthermore, it was found that electrolytes that typically perform poorly in battery cells with alloy-type anodes of conventional nanoscale sizes (e.g., in the range of about 1 nm to about 200 nm) perform significantly better in battery cells containing high-capacity (nano)composite anode particles (e.g., powders). These high-capacity (nano)composite anode particles exhibit a moderately high volume change (e.g., about 8 vol% to about 180 vol%) during the first charge-discharge cycle and a moderate volume change (e.g., about 4 vol% to about 50 vol%) during subsequent charge-discharge cycles, with an average size in the range of about 0.2 μm to about 40 μm. It was found that for certain applications, variations in electrolyte composition have a particularly strong impact on the improved battery cell performance achieved by using such (nano)composite anodes containing alloy-type anode materials. In particular, it was found that electrolyte compositions designed to improve the performance of subclasses of such anode powders are particularly valuable and influential for achieving a combination of good stability, good energy density, and other performance characteristics, wherein the specific surface area of ​​the anode powder is about 0.5 m². 2 / g to approximately 50m 2 In one instance, for silicon (Si)-containing anode materials, (nano)composite electrodes with a weight capacity in the range of about 600 mAh / g to about 2200 mAh / g or about 2600 mAh / g (normalized by the total mass of the combined (nano)composite particles, binder and conductive additives) are particularly valuable because the combination of the disclosed electrolyte composition with such an anode allows the battery cell to achieve an attractive combination of good stability, good energy density, good rate performance and other important and desired performance characteristics.

[0032] For a wide range of batteries, one or more embodiments of this disclosure overcome some of the challenges discussed above in various types of battery cells comprising nanocomposite anode materials (e.g., materials including conversion-type and alloy-type active materials), which undergo a certain volume change during cycling (e.g., a moderately high volume change during the first charge-discharge cycle (e.g., about 8 vol% to about 160 vol% or about 180 vol%), and a moderate volume change during subsequent charge-discharge cycles (e.g., about 4 vol% to about 50 vol%)), have an average particle size in the range of about 0.2 micrometers to about 40 micrometers, and a specific surface area of ​​about 0.5 m². 2 / g to approximately 50m 2 Within the range of / g. Depending on one or more embodiments, it can be used in the medium (e.g., about 2mAh / cm³) range. 2 Approximately 4mAh / cm 2 ) and high capacity load (e.g., approximately 4 mAh / cm³) 2 Approximately 10mAh / cm 2 Electrodes with high packing density (e.g., after the first charge-discharge cycle, the porosity of the electrolyte-filled electrode is in the range of about 5 vol% to about 35 vol%) and relatively low binder content (e.g., about 0.5 wt% to about 14 wt%) are used to formulate substantially more stable battery cells.

[0033] The conventional cathode materials used in Li-ion batteries are intercalated and typically crystalline. Such cathodes typically exhibit a peak charging potential of less than approximately 4.3V relative to Li / Li+, a gravimetric capacity of less than approximately 190 mAh / g (based on the mass of the active material), and a capacity of less than approximately 800 mAh / cm³. 3 The volumetric capacity (based on the volume of the electrode, excluding the volume occupied by the current collector foil). For a given negative electrode, higher energy densities in Li-ion batteries can be achieved by using a high-voltage positive electrode (with a maximum charging potential ranging from approximately 4.35 V to approximately 5.1 V relative to Li / Li+) or by using so-called conversion-type positive electrode materials (including, but not limited to, those containing F or S in their composition). Some high-voltage intercalation positive electrodes may contain nickel (Ni). Some high-voltage intercalation positive electrodes may contain manganese (Mn). Some high-voltage intercalation positive electrodes may contain cobalt (Co). In some designs, high-voltage intercalation positive electrode particles may contain fluorine (F) in their structure or surface layer. Some high-voltage intercalation positive electrodes may contain phosphorus (P). The combination of such high-energy-density positive electrodes with high-capacity (e.g., Si-based) negative electrodes can result in high cell-level energy densities. Unfortunately, at least when used in combination with conventional electrolytes, the cycle stability and other performance characteristics of such cells may be insufficient for some applications.

[0034] Therefore, one or more embodiments of this disclosure relate to electrolyte compositions for a subclass of high-voltage intercalation positive electrodes (with a maximum charging potential in the range of about 4.2 V to about 4.5 V relative to Li / Li+, and in some cases, in the range of about 4.5 V to about 5.1 V relative to Li / Li+) and high-capacity negative electrodes with moderate volume change (e.g., negative electrodes comprising (nano)composite negative electrode powder, which exhibits a suitably high volume change (e.g., about 8 vol% to about 160 vol% or about 180 vol%) during the first charge-discharge cycle, and a moderate volume change (e.g., about 4 vol% to about 50 vol%) during subsequent charge-discharge cycles), with an average particle size (e.g., average diameter) in the range of about 0.2 μm to about 40 μm, and a specific surface area of ​​about 0.5 m². 2 / g to approximately 50m 2 Within the range of / g, the specific surface area is normalized by the mass of the composite electrode particles, and in the case of a Si anode, the specific capacity exhibits good performance in a combination of about 550 mAh / g to about 2200 mAh / g or about 2700 mAh / g (when normalized by the total mass of the composite anode particles, conductive additives, and binder), or in a range of about 650 mAh / g to about 2200 mAh / g or about 2900 mAh / g (when normalized only by the mass of the composite anode particles). In at least one embodiment, a specific electrolyte composition can be selected based on the value of the highest positive charge potential.

[0035] Examples of high specific capacity and high volumetric capacity conversion cathode materials include, but are not limited to, fluorides, chlorides, sulfides, and selenides. For example, fluoride-based cathodes are particularly valuable due to their extremely high capacity (exceeding 300 mAh / g in some cases and greater than 1200 mAh / cm² at the electrode level). 3Lithium can provide excellent technical potential. For example, in the absence of Li, the theoretical specific capacity of FeF3 is 712 mAh / g; FeF2 is 571 mAh / g; MnF3 is 719 mAh / g; CuF2 is 528 mAh / g; NiF2 is 554 mAh / g; PbF2 is 219 mAh / g; BiF3 is 302 mAh / g; BiF5 is 441 mAh / g; SnF2 is 342 mAh / g; SnF4 is 551 mAh / g; SbF3 is 450 mAh / g; SbF5 is 618 mAh / g; CdF2 is 356 mAh / g; and ZnF2 is 519 mAh / g. AgF and AgF2 also offer theoretical specific capacity and additionally exhibit very high lithiation potential. Mixtures of fluorides (e.g., in alloy form) can provide theoretical capacities approximately calculated according to mixture rules. Using mixed metal fluorides can sometimes be advantageous (e.g., providing higher rate capability, lower resistance, higher practical capacity, or longer stability). Using metal fluorides mixed with metals can also sometimes be advantageous (e.g., providing higher rate capability, lower resistance, higher practical capacity, or longer stability). In the fully lithilated state, metal fluorides are converted into composite materials containing a mixture of metal and LiF clusters (or nanoparticles). Examples of the overall reversible reaction of the conversion metal fluoride cathode can include: for CuF2-based cathodes, 2Li + CuF2 ↔ 2LiF + Cu, or for FeF3-based cathodes, 3Li + FeF3 ↔ 3LiF + Fe. It should be understood that metal fluoride-based cathodes can be prepared in either Li-free, partially lithilated, or fully lithilated states. Another promising example of a conversion-type cathode (or, in some cases, anode) material is sulfur (S) (in the Li-free state) or lithium sulfide (Li2S, in the fully lithiated state). To reduce the dissolution of the active material during cycling to improve conductivity or mechanical stability of the S / Li2S electrode, porous S, Li2S, porous S-C composites, Li2S-C composites, porous S polymer composites, or other composites containing S or Li2S or both can be utilized.

[0036] Note that in some designs, different electrolyte compositions can provide the most favorable performance for battery cells that include the same negative electrode (e.g., a Si-containing nanocomposite negative electrode) and different positive electrodes (intercalation type, high-voltage intercalation type, S-containing conversion type, fluorine-containing conversion type, etc.).

[0037] Unfortunately, many conversion electrodes used in Li-ion batteries suffer from performance limitations. The formation of (nano)composites can at least partially overcome these limitations. For example, certain (nano)composites can provide reduced voltage hysteresis, improved capacity utilization, improved rate performance, improved mechanical stability, and sometimes improved electrochemical stability, reduced volume change, and / or other positive properties. Examples of such composite cathode materials include, but are not limited to: LiF-Cu-Fe-C nanocomposites, LiF-Cu-Fe-Ag-C nanocomposites, LiF-Cu-Fe-Ti-C nanocomposites, LiF-Cu-Fe-Mn-C nanocomposites, FeF2-C nanocomposites, FeF3-C nanocomposites, CuF2-C nanocomposites, CuF2-C-AlF3 nanocomposites, CuF2-C-Al2O3 nanocomposites, LiF-Cu-C nanocomposites, LiF-Cu-C polymer nanocomposites, and LiF-C... u-another metal-C-polymer nanocomposites, LiF-Cu-another metal oxide-C-polymer nanocomposites, LiF-Cu-another metal fluoride-C-polymer nanocomposites, LiF-Cu-metal-polymer nanocomposites, and many other porous nanocomposites, including LiF, FeF3, FeF2, MnF3, CuF2, NiF2, PbF2, BiF3, BiF5, CoF2, SnF2, SnF4, SbF3, SbF5, CdF2, ZnF2, AgF, AlF3, AgF2, or other metal fluorides or mixtures thereof. Such composites may also contain oxides and fluorine oxides, and may contain conductive (primarily sp) 2(Bonded) carbon. In some instances, metal fluoride nanoparticles can permeate into the pores of porous carbon (e.g., into the pores of activated carbon particles) to form these metal fluoride-C or mixed metal-LiF-another metal oxide or metal fluoride-C nanocomposites, and other related compositions. In particular, high-capacity (nano)composite cathode particles (e.g., powders) may be particularly attractive for battery applications in terms of manufacturability and performance characteristics, wherein said high-capacity (nano)composite cathode particles exhibit a reasonably high (for cathode) volume change (e.g., about 5 vol% to about 100 vol%) during the first charge-discharge cycle, a moderate volume change (e.g., about 4 vol% to about 50 vol%) during subsequent charge-discharge cycles, and an average size (e.g., diameter in the case of spherical particles, or thickness in the case of flat or granular particles, or average size in the case of randomly shaped particles) in the range of about 0.2 micrometers to about 40 micrometers. In some designs, the near-spherical (globose) shape of composite cathode particles is particularly attractive for optimizing the rate performance and volumetric capacity of the electrode. While some improvements can be achieved through the formation and utilization of such transformative nanocomposite cathode materials and electrode optimization, further improvements in battery cell performance characteristics can be achieved by modifying the composition and preparation of the electrolyte, beyond what is known or shown by conventional prior art.

[0038] Therefore, one or more embodiments of this disclosure relate to electrolyte compositions that are suitable for: (i) high-capacity conversion (nano)composite cathode materials, which exhibit moderate volume change (e.g., about 5 vol% to about 50 vol%) during the first charge-discharge cycle, small to moderate volume change (e.g., about 3 vol% to about 40 vol%) during subsequent charge-discharge cycles, and an average size (e.g., diameter in the case of spherical particles) of about 0.2 micrometers to about 4 micrometers. Within the 0 micrometer range, the subclass of (ii) high-capacity, moderate-volume-change negative electrodes includes negative electrodes comprising (nano)composite negative electrode powder that exhibits a suitably high volume change (e.g., about 8 vol% to about 160 vol% or about 180 vol%) during the first charge-discharge cycle, and a moderate volume change (e.g., about 4 vol% to about 50 vol%) during subsequent charge-discharge cycles, with an average size (e.g., average diameter) in the range of about 0.2 micrometers to about 40 micrometers, and a specific surface area in the range of about 0.5 m². 2 / g to approximately 50m 2Within the range of / g, the specific surface area is normalized by the mass of the active electrode particles, and in the case of a Si anode, its specific capacity exhibits good performance in the range of about 550 mAh / g to about 2200 mAh / g or about 2700 mAh / g (when normalized by the total mass of the composite electrode particles, conductive additives and binder), or in the range of about 650 mAh / g to about 2200 mAh / g or about 2900 mAh / g (when normalized by the mass of the composite anode particles alone)).

[0039] The inventors have discovered that battery cells comprising electrodes based on high-capacity nanocomposite particles or powders (containing conversion or alloying active materials) can benefit from specific electrolyte compositions that provide significantly improved performance, particularly for high capacity loads, wherein the high-capacity nanocomposite particles or powders undergo a certain volume change during cycling (a moderately high volume change during the first charge-discharge cycle (e.g., an increase of about 8 vol% to about 180 vol%, or a decrease of about 8 vol% to about 70 vol%), and a moderate volume change during subsequent charge-discharge cycles (e.g., about 4 vol% to about 50 vol%)), and the average size is in the range of about 0.2 micrometers to about 40 micrometers (e.g., Si-based nanocomposite anode powders, etc.).

[0040] For example, (i) the continuous volume change of high-capacity nanocomposite particles during cycling combined with (ii) electrolyte decomposition on the surface of the conductive electrode at the electrode operating potential (e.g., primarily reduction of the electrochemical electrolyte in the case of a Si-based anode) can lead to continuous (even relatively slow) growth of the solid electrolyte phase interface (SEI) layer on the surface of the nanocomposite particles, resulting in irreversible loss of battery cell capacity.

[0041] The swelling of the binder in the electrolyte depends not only on the composition of the binder but also potentially on the composition of the electrolyte. Furthermore, such swelling (and the resulting performance degradation) is generally associated with a decrease in the elastic modulus of the binder upon exposure to the electrolyte. In this sense, the smaller the modulus reduction in certain electrolytes, the more stable the interface between the binder-bonded (nano)composite active particles / conductive additives becomes. A reduction in binder modulus exceeding 15% to 20% can lead to a significant performance degradation. In one instance, a two-fold reduction in binder modulus (a 2x decrease) can result in a substantial performance degradation. In another instance, a five-fold or greater reduction (e.g., a 5x to 500x decrease) can result in a very significant performance degradation. Therefore, for certain applications, selecting an electrolyte composition that does not cause significant binder swelling may be highly preferred. In some instances, it may be preferable to select an electrolyte composition such that, upon exposure to the electrolyte, the reduction in binder modulus is less than about 30% by volume (more preferably, no more than 10% by volume). In a negative electrode comprising more than one binder composition, it may be preferred to select an electrolyte composition in which at least one binder does not reduce the modulus by more than 30% by volume (more preferably, no more than 10% by volume) when exposed to an electrolyte.

[0042] The following electrolyte compositions may be advantageous for use in Li and Li-ion battery cells having high-capacity nanocomposite electrode powders (containing conversion or alloying active materials), wherein the high-capacity nanocomposite electrode powders undergo a certain volume change during cycling (a suitably high volume change during the first charge-discharge cycle (e.g., an increase of about 8 vol% to about 160 vol% or about 180 vol%, or a decrease of about 8 vol% to about 70 vol%), and a moderate volume change during subsequent charge-discharge cycles (e.g., about 4 vol% to about 50 vol%)), have an average size in the range of about 0.2 micrometers to about 40 micrometers (more preferably about 0.4 micrometers to about 20 micrometers for some applications), and a specific surface area of ​​about 0.5 m². 2 / g to approximately 50m 2Within the range of / g. These electrolytes may contain one or more of the following components: (a) a low melting point (LMP) solvent or solvent mixture; (b) a conventional melting point (RMP) solvent or solvent mixture; (c) an additive (ADD) solvent or solvent mixture (e.g., added to improve the interfacial properties of the negative electrode electrolyte or the positive electrode electrolyte or to stabilize the Li salt or to provide other useful functions); (d) a main (MN) Li salt or Li salt mixture; (e) an additive (ADD) salt or salt mixture (not necessarily Li-based) (e.g., added to improve the interfacial properties of the negative electrode electrolyte or the positive electrode electrolyte or to stabilize the Li salt or to provide other useful functions); (f) other functional additives (OFADD) (e.g., added to enhance the safety of the battery cell), wherein the LMP solvent or LMP solvent mixture may preferably be The LMP solvent or solvent mixture preferably comprises about 10% to about 95% of the total solvent volume in the electrolyte (more preferably, in some designs, the LMP solvent or LMP solvent mixture may comprise about 10% to about 80% of the total solvent volume in the electrolyte; for example, for a battery cell with a high-capacity nanostructured anode, a more advantageous LMP solvent volume fraction may be in the range of about 20% to about 60%); wherein the RMP solvent or RMP solvent mixture may preferably comprise about 5% to about 90% of the total solvent volume in the electrolyte (more preferably, in some designs, the RMP solvent or RMP solvent mixture may comprise about 20% to about 90% of the total solvent volume in the electrolyte); and wherein the ADD solvent or solvent mixture may preferably comprise about 0% to about 6% of the total solvent volume in the electrolyte. For a particular application, the specific values ​​of the optimal volume fractions of the LMP, RMP, and ADD solvents or solvent mixtures may depend on the battery cell operating potential required for the battery cell in a given application, the battery cell operating (or battery cell storage) temperature, and the charge / discharge rate. Examples of suitable esters for use as one or more LMP solvents or co-solvents may include, but are not limited to: various formate esters (e.g., methyl formate, ethyl formate, propyl formate, butyl formate, amyl formate, hexyl formate, heptyl formate, etc.), various acetate esters (e.g., methyl acetate, ethyl acetate, propyl acetate, butyl acetate, amyl acetate, hexyl acetate, heptyl acetate, etc.), and various propionate esters (e.g., Methyl propionate, propionic acid Ethyl acetate, propyl propionate, butyl propionateThis includes various butyrate esters (e.g., methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, pentyl butyrate, hexyl butyrate, heptayl butyrate, etc.), various valerate esters (e.g., methyl valerate, ethyl valerate, propyl valerate, butyl valerate, pentyl valerate, hexyl valerate, heptayl valerate, etc.), various hexanoate esters (e.g., methyl hexanoate, ethyl hexanoate, propyl hexanoate, butyl hexanoate, pentyl hexanoate, hexyl hexanoate, heptayl hexanoate, etc.), and various heptaester esters (e.g., methyl heptaate, ethyl heptaate, propyl heptaate). The list includes butyl heptaate, pentyl heptaate, hexyl heptaate, heptaate, etc.), various octanoic acid esters (e.g., methyl octanoate, ethyl octanoate, propyl octanoate, butyl octanoate, pentyl octanoate, hexyl octanoate, heptaate, etc.), various nonanoic acid esters (e.g., methyl nonanoate, ethyl nonanoate, propyl nonanoate, butyl nonanoate, pentyl nonanoate, hexyl nonanoate, heptaate, etc.), various decanoic acid esters (e.g., methyl decanoate, ethyl decanoate, propyl decanoate, butyl decanoate, pentyl decanoate, hexyl decanoate, heptaate, etc.), and fluorinated forms of the above esters, which are merely examples. Examples of solvents suitable for use as RMP solvents in electrolytes (or for manufacturing mixtures of RMP solvents in electrolytes) may include: various carbonates (fluorinated acyclic carbonates and propylene carbonates are particularly advantageous for use in battery cells with high-voltage positive electrodes), various sulfones (e.g., dimethyl sulfone, ethyl methyl sulfone, etc.) and various sulfoxides, various lactones, various phosphorus-based solvents (e.g., dimethyl methylphosphonate, triphenyl phosphate, etc.), various silicon-based solvents, various types of higher melting point esters (e.g., esters with melting points above about -50°C), various ethers (e.g., dioxopentane, monoethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and polyethylene oxide, etc.), various cyclic ester molecules (e.g., butyrolactone and valerate), various dinitriles (e.g., succinate, adiponitrile and glutaronitrile), and various ionic liquids (e.g., imidazolium, pyrrolidone, piperidinium, etc., which may be particularly useful in battery cells containing high-voltage positive electrodes). One or more RMP solvents can also be fluorinated (fully or partially). The most widely used fluorinated solvent (in Li-ion batteries) is fluoroethylene carbonate (FEC). It helps to form a more stable (more cross-linked) SEI compared to ethylene carbonate EC, but excessive use (e.g., above about 30% by volume) can also lead to degraded battery cell performance, especially at high temperatures and / or in battery cells containing a high-voltage cathode operating at a voltage above about 4.2V relative to Li / Li+. Examples of solvents suitable for use as ADD solvents in electrolytes (or for manufacturing mixtures of ADD solvents in electrolytes) can include a variety of carbonates (including fluorinated carbonates), a variety of sulfones (including fluorinated sulfones), a variety of sulfoxides (including fluorinated sulfoxides), a variety of lactones (including fluorinated lactones), a variety of phosphorus-based solvents (including fluorinated phosphorus-based solvents), a variety of silicon-based solvents (including fluorinated silicon-based solvents), and a variety of ethers (including fluorinated ethers), a variety of nitriles and dinitriles, etc.Nitriles and dinitriles typically form unfavorable SEIs on the negative electrode, but their application in small amounts (e.g., typically less than 10% by volume, more often less than 5% by volume) in the electrolyte mixture can improve the electrolyte conductivity and cell performance, especially when using a high-voltage positive electrode. In some cases (e.g., when a high (e.g., above 20% by volume) content of so-called “SEI forming agents” is used in the electrolyte), nitriles and dinitriles can also be components of the LMP solvent mixture.

[0043] As used herein, LMP refers to a melting point (of a solvent or solvent mixture) that is generally below a threshold (e.g., below -60°C) and generally in the range, for example, from about -120°C to about -60°C. RMP refers to a melting point (of a solvent or solvent mixture) that is generally above a threshold (e.g., above -60°C) and generally in the range, for example, from about -60°C to about +30°C. In another instance, LMP may refer to a melting point (of a solvent or solvent mixture) within a narrower range, such as from about -110°C to about -70°C, or from about -100°C to about -80°C.

[0044] In one or more embodiments of the invention, it may be further advantageous that the boiling point of one or more LMP solvents (or at least one major component of a mixture of LMP solvents) in the electrolyte exceeds about +50°C (more preferably, exceeds about +70°C; even more preferably, exceeds about +80°C).

[0045] The following provides further discussion on battery cells having the same type of high-capacity nanocomposite electrode particles or powders as those described above (e.g., high-capacity nanocomposite negative electrode powder of the same type / category in the negative electrode; or high-capacity nanocomposite positive electrode powder of the same type / category).

[0046] In some designs, multiple cyclic or linear esters (e.g., γ-valerolactone, γ-methylene-γ-butyrolactone, γ-caprolactone, α-angelicolactone, α-methylene-γ-butyrolactone, ε-caprolactone, 5,6-dihydro-2H-pyran-2-one, γ-butyrolactone, δ-caprolactone, α-methyl-γ-butyrolactone, tetrachlorophthalide, γ-caprolactone, ethyl propionate, propyl acetate, methyl formate, ethyl acetate, propyl propionate, methyl propionate, ethyl propionate, methyl valerate, etc.) Methyl butyrate, ethyl butyrate, butyl valerate, butyl butyrate, propyl propionate, etc. (In some designs, they do not contain functional groups, while in others they contain other functional groups (e.g., halogens, alcohols, alkanes, alkenes, alkynes, ketones, aldehydes, ethers, amines, amides, imides, nitriles, sulfonyl groups, carboxylic acids, phosphate esters, etc.)), various cyclic or straight-chain ethers (e.g., tetrahydrofuran, tetrahydropyran, furan, 4-methylpyran, pyran, 12-crown-4, 15-crown-5, etc.). 18-crown-6, 4-methyl-1,3-dioxane, dimethyl ether, methyl tert-butyl ether, diethyl ether, methoxyethane, dioxane, dioxane, dioxolane, monoethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc. (In some designs, they do not contain functional groups, while in others they contain other functional groups (e.g., halogens, alcohols, alkanes, alkenes, alkynes, ketones, aldehydes, ethers, amines, amides, imides, nitriles, sulfonyl groups, carboxylic acids, phosphate esters, etc.)), various acids Anhydrides (e.g., glutaric anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, cyclobutane-1,2,3,4-tetracarboxylic anhydride, butyric anhydride, isobutyric anhydride, etc.) (in some designs, they do not contain functional groups, while in others they contain additional functional groups (e.g., halogens, alcohols, alkanes, alkenes, alkynes, ketones, aldehydes, ethers, amines, amides, imides, nitriles, sulfonyl groups, carboxylic acids, phosphate esters, etc.)) can be advantageously used as LMP solvents or co-solvents in LMP mixtures.

[0047] In some designs and applications, adding different functional groups to the selected electrolyte solvent (e.g., at least some solvents from (one or more) LMPs or mixtures of LMPs, such as anhydrides, ethers, esters, etc., or from RMPs or mixtures of RMPs) can provide a variety of advantages. For example, adding (one or more) electron-donating materials (such as alkanes, methoxy groups, amines, etc.) can lower the reduction potential (i.e., make it more difficult to reduce), which can be advantageous when it is necessary to avoid or minimize such reduction of a particular solvent (e.g., when such solvents are not used to form the SEI, but are added to maintain high ionic conductivity within the electrode pores at the cell operating temperature). In another instance, adding (one or more) electron-withdrawing materials (such as fluorine, esters, nitro groups, etc.) can increase the solvent reduction potential (make it easier to reduce), which can be advantageous when such solvents are used as components for stable SEI formation. In one instance, the formation of such an SEI at an elevated potential (before other electrolyte solvent components are reduced) can prevent undesirable reduction by other solvents on the electrode surface (e.g., solvents that form less stable SEIs, SEIs with low ionic conductivity, or SEIs with other less favorable characteristics). Furthermore, if the cathode is exposed to a high electrode potential (e.g., above approximately 4.4 V relative to Li / Li+), such a solvent can provide a higher oxidation potential (which is beneficial for maintaining improved stability and reducing leakage rates, etc.).

[0048] In the case of one or more electron-withdrawing materials, in some designs, it may be particularly advantageous to replace selected hydrogen atoms in such solvents or co-solvents with fluorine atoms (e.g., through the use of various fluorination reactions or other mechanisms). Specifically, electrolyte solvents / co-solvents (e.g., components of LMP and / or RMP electrolyte solvent components) that have already performed well in applications (e.g., forming a slightly stable SEI) can additionally benefit (e.g., exhibiting increased cycle stability or other benefits) from at least partial fluorination, especially if high-capacity nanostructured anodes (e.g., Si-containing anodes) are used in the battery construction. Such reactions can increase the SEI formation potential and enhance the electrochemical stability of the electrode during cycling (e.g., enhanced stability through a protective anode SEI or cathode SEI layer). Suitable examples include various fluorinated esters, various fluorinated ethers, various fluorinated anhydrides in the case of LMP components, and various other fluorinated solvents (including carbonates, nitriles, sulfones, larger esters, etc.) in the case of RMP components. It should be understood that the optimal fluorination action or content of the fluorinated solvent can vary depending on the application. For example, in some applications (e.g., where the battery positive electrode may be exposed to high temperatures (e.g., above about 40°C) and high operating potentials (e.g., above about 4.4V relative to Li / Li+)), over-fluorination or the use of excessive fluorinated solvents may be undesirable. Furthermore, over-fluorination or the use of excessive fluorinated solvents can reduce the electrolyte wettability of some separators or electrodes, thereby reducing capacity utilization and rate performance, especially at lower temperatures. The optimal amount of fluorinated solvent can depend on the operation of the battery cell, as well as the chemical composition and properties of the electrode and separator surfaces.

[0049] In some designs, the use of solvents (co-solvents) that have double bonds in their structure (e.g., one, fewer, or more than one double bond per solvent molecule) (e.g., as a component of the electrolyte solvent component in LMP or RMP) or other opportunities to form polymers via chemical or electrochemical reactions may favor the formation of a more stable SEI (e.g., through olefin polymerization). Solvent molecules containing both double bonds and fluorine can be particularly attractive for forming SEIs with favorable properties (e.g., improved stability, etc.). Similarly, solvents (co-solvents) that can undergo ring-opening polymerization (e.g., in solvents with ring structures containing olefins or multiple heteroatoms, such as propane sulfone) can also be advantageously used as electrolyte components because they can form a more stable SEI in some designs.

[0050] The polarity of a solvent (co-solvent), influenced by its functional groups, can significantly affect the properties of an electrolyte. For example, a more polar solvent can provide higher solubility for electrolyte salts, thus contributing to improved ionic conductivity. However, more polar solvents are generally more difficult (and more expensive) to dry (remove residual moisture). Furthermore, many polar solvents (such as amines and alcohols) can be sources of protons, potentially causing undesirable side reactions (e.g., hydrogen evolution).

[0051] In some designs, it may be advantageous to have a solvent mixture in the electrolyte, where one or more solvents exhibit a wide electrochemical stability window, while one or more other solvents exhibit a narrower electrochemical stability window (at least when combined with the electrolyte salt). In some designs, it may be advantageous to have at least some of the electrolyte solvents exhibiting electrochemical stability windows that differ by more than about 1 V. In some designs, it may be advantageous to have at least one component of the LMP solvent mixture exhibit a higher electrochemical stability window than at least one component of the RMP solvent mixture (at least when used with the same electrolyte salt).

[0052] Figure 2 Selected examples of linear ester solvents (without additional functional groups) having their melting point and other properties (such as boiling point, flash point, refractive index) are shown, which can be effectively used as LMP (or RMP) components of suitable electrolyte compositions according to embodiments of this disclosure.

[0053] Figure 3A and 3B An illustrative example of selected performance characteristics of a matched full cell is shown, comprising an intercalated lithium iron phosphate (LFP) powder cathode and a high-capacity nanocomposite Si-containing powder anode. The cell cycled within a potential range of 1.85 V to 3.65 V. The nanocomposite anode exhibited moderate to high volume change during the first charge-discharge cycle and moderate volume change during subsequent charge-discharge cycles. The average particle size of individual anode particles was approximately 3 micrometers, with a specific surface area of ​​approximately 5 m². 2 / g. The negative electrode coating comprises 92 wt% nanocomposite negative electrode powder and 8 wt% inactive components (binder and conductive additives). The battery cell electrolyte comprises 2 vol% vinylene carbonate (VC) (as an ADD electrolyte component), 40 vol% a mixture of cyclic and linear carbonates (20 vol% each) (as the RMP component of the electrolyte), and a very high content (up to 58 vol%) of methyl butyrate (MB) (as a linear ester and LMP component of the electrolyte; methyl butyrate has a very low melting point of approximately -95°C). Cycle stability is described by the specific capacity of the negative electrode active material. Figure 3ATypical charge-discharge curves are shown for cycle 1 (upper charge capacity curve) and cycle 5 (lower charge capacity curve due to irreversible first-cycle losses). This exemplary battery cell exhibits a first-cycle charge-discharge efficiency of 88%. Figure 3B The electrochemical stability of an exemplary battery cell is shown, where the specific capacity is normalized by the weight of the active negative electrode material (92 wt% of the weight of the negative electrode coating). The battery cell is cycled at 0.5C at room temperature and a cycle life of approximately 940 cycles (reaching 80% of the capacity at cycle 5) is shown.

[0054] In some designs, it may be advantageous to have a total salt concentration in the electrolyte in the range of about 0.8 M to about 2.0 M when using a mixture of two or more salts. Salt concentrations in the electrolyte below about 0.8 M may lead to reduced cell stability (e.g., when using high-capacity negative electrode materials), particularly when using high areal capacity electrodes (e.g., above about 4 mAh / cm²). 2 A high salt concentration in the electrolyte can lead to reduced rate performance and, in some designs, decreased cell stability. This reduced performance characteristic may be related to the Li content in the electrolyte. + The reduced cation mobility is associated with this. Higher salt concentrations can also lead to increased electrolyte density and cost, which may be undesirable for some applications. The optimal salt concentration can depend on the specific battery cell design and electrolyte composition. Interestingly, some battery cells (e.g., those including Li₂S or Li₂Se or S or Se-based conversion cathodes or Li metal anodes, etc.) can sometimes (e.g., when fast charging is not required) benefit from a reduced electrolyte molar concentration (e.g., below about 0.2 M).

[0055] In some cases, combinations of salts can exhibit enhanced Li compared to single salts of the same concentration. + Mobility. In some designs, salts can be chosen such that the Li salt (or its solvated counterpart) forms a eutectic system (with a reduced melting point). In one example, several Li imide salts (e.g., SO2FN) − (Li + SO2F and CF3SO2N − (Li + A mixture of SO2CF3 salts, or CF3SO2N − (Li + SO2CF3 and CF3CF2SO2N − (Li + A mixture of SO2 and CF3, or CF3SO2N − (Li +SO2CF3 and CF3CF2SO2N − (Li + Mixtures of SO2, CF2, and CF3, etc., can form such systems. In some designs, the salt and its relative fraction can be selected to induce a lower freezing point. In some designs, the most favorable relative fraction of the salt can be selected to minimize the freezing point (achieved through such a lower freezing point). In some designs, small amounts (e.g., from about 0.001 M to about 0.500 M) of other Li salts and non-Li salts can be added to further lower the electrolyte melting point, improve SEI properties, and reduce the solubility of the active material or its components. In some designs, the non-Li salt can be a salt of Mg, K, Ca, or Na. In some designs, the non-Li salt can be a salt of a rare earth metal (e.g., La).

[0056] In some designs using two or more salts (e.g., three, four, or five salts, etc.), it may be advantageous that at least one salt contains LiPF6 (in the case of rechargeable Li or Li-ion batteries). In some designs, it may be further advantageous that another salt is also a Li salt. It may be further advantageous that at least one other (non-LiPF6) salt is electrochemically unstable in the electrolyte (e.g., decomposes at the negative electrode) when the negative electrode potential is reduced to below about 0.3V to 2.3V relative to Li / Li+. In some designs, it may be advantageous that salt decomposition occurs above about 0.3V relative to Li / Li+, more preferably above about 1V relative to Li / Li+ (and in some designs, more preferably above about 1.5V relative to Li / Li+). It may be further advantageous that the non-LiPF6 salt in the electrolyte induces or catalyzes electrolyte reduction at a voltage relative to Li / Li+ greater than about 0.3 V, more preferably greater than about 1 V (and in some designs, more preferably greater than about 1.5 V or even greater than about 2.0 V) relative to Li / Li+. It may also be further advantageous that the (e.g., partially decomposed) non-LiPF6 salt in the electrolyte reacts with at least some solvent molecules in the electrolyte to form oligomers. In some designs, the non-LiPF6 salt may be a LiFSI salt. Furthermore, when the electrolyte contains both LiPF6 and LiFSI salts, the molar ratio of the LiPF6 salt to the LiFSI salt is preferably in the range of about 100:1 to about 1:1. The exact optimal ratio may depend on electrode characteristics (e.g., thickness, amount of binder, density, composition and capacity of the negative and positive electrodes, etc.), the electrolyte solvent mixture used, and the cycling method (temperature, cell voltage range, etc.). It may be further advantageous that the electrolyte solvent comprises a mixture of LMP and RMP solvents, as well as (optionally) ADD and other co-solvents. In some designs, it may also be advantageous that the LMP solvent or solvent mixture comprises (one or more) esters.

[0057] In some designs, it may be advantageous to maintain a total salt concentration in the electrolyte in the range of about 0.8 M to about 2.0 M, while using a small fraction of at least one at least partially fluorinated solvent in the electrolyte mixture, in the range of about 1 vol% to about 30 vol%, as a fraction of all solvents in the electrolyte. It may be further advantageous that the electrolyte solvent mixture comprises both linear and cyclic molecules. It may be advantageous that at least one cyclic molecule comprises a fluorine atom. In some designs, it may be preferred that the electrolyte contains a fluoroethylene carbonate (FEC) co-solvent (e.g., in the range of about 1 vol% to about 30 vol%, as a fraction of all solvents in the electrolyte). In one instance, the optimal amount of FEC may depend on the surface area of ​​the nanostructured anode particles. For particles with a lower surface area (e.g., less than about 15 m²), the optimal amount of FEC may be less desirable. 2 For nanostructured anode particles with a surface area of ​​approximately 15 m² / g, the FEC content may not significantly affect the formation efficiency. However, for particles with a high surface area (e.g., above approximately 15 m² / g), the FEC content may not significantly affect the formation efficiency. 2 For particles of ( / g), a higher FEC content can improve formation efficiency. Lower surface area and smaller volume changes may also require a smaller FEC fraction for stable operation. Higher FEC content (e.g., above 20 vol% to 30 vol%) may reduce cell performance at high temperatures (e.g., above about 35°C), especially if the cell's positive electrode is exposed to a high potential (e.g., above about 4.3V to 4.4V relative to Li / Li+). It may be further advantageous that the electrolyte solvent comprises a mixture of LMP and RMP solvents and (optionally) ADD solvent. In some designs, it may also be advantageous that the LMP solvent or solvent mixture comprises (one or more) esters. In some designs, it may also be advantageous that the electrolyte contains other cyclic carbonates in addition to FEC (or other fluorinated cyclic carbonates). In some designs, it may be advantageous that the other cyclic carbonates comprise ethylene carbonate (EC) with a melting point of about +34°C to 37°C or another cyclic carbonate with a high melting point (e.g., above about +25°C). Furthermore, the volume ratio of FEC (or other fluorinated cyclic carbonates) to other cyclic carbonates can preferably be in the range of about 9:1 to about 1:50. The exact optimal ratio may depend on electrode characteristics (e.g., thickness, amount of binder, density, composition and capacity of the negative and positive electrodes, etc.), the electrolyte solvent mixture used, and the battery cell cycling method (temperature, voltage range, etc.).

[0058] Figures 4A to 4BThe effects of several exemplary electrolyte compositions on battery cell performance are illustrated. These cells comprise a powder-based high-capacity, Si-containing nanocomposite anode and a powder-based intercalation cathode (lithium cobalt oxide, LCO in this example), and are cycled over a voltage range of 2.5V to 4.4V. Cycling stability was investigated in several exemplary cells cycled at a “C / 2” rate. Two to three (2 to 3) nearly identical battery cells were constructed, and their consistency was tested. In these examples, all electrolytes contained 1.2M of the same salt (LiPF6) and 58% by volume (as a fraction of total solvent volume) selected from… Figure 2 The ester (melting point below -90°C), 2% by volume of the same ADD cyclic carbonate solvent, 20% by volume of the same linear carbonate and a variable FEC (in the range of 0% to 30% by volume) and a variable other cyclic carbonate (EC) (in the range of 0% to 30% by volume) to keep the total amount of cyclic carbonate constant at 30% by volume. Figure 4A This indicates that nanostructured Si anodes with higher surface areas exhibit lower first charge-discharge cycle efficiency (e.g., corresponding to...). Figure 4A The data points in the lower part of the curves) and the strong dependence of efficiency on the FEC fraction. Nanostructured Si anodes with lower surface area exhibit higher first-cycle efficiency (e.g., corresponding to...). Figure 4A (Data points in the upper middle curve) and the weak dependence of efficiency on the FEC score. Figure 4B The performance of Li-ion battery cells with Si-containing anodes at room temperature and 45°C is shown, and it is illustrated that for almost identical battery cells with nearly identical Si-containing anodes, (in this example) a FEC content of less than about 20 vol% reduces the cycle stability of the battery cell at room temperature (e.g., corresponding to...). Figure 4B (Data points in the upper part of the curve), while an FEC content greater than approximately 20% by volume slightly reduced stability at 45°C (e.g., corresponding to...). Figure 4B Data points of the lower middle curve.

[0059] The area electrode capacity is higher than approximately 4 mAh / cm². 2In some designs, it may be advantageous to have a total Li salt concentration in the electrolyte exceeding about 1 M (preferably exceeding about 1.1 M, exceeding about 1.2 M in some designs, and below about 2.4 M; below about 1.8 M in some designs), while using a small fraction of at least one at least partially fluorinated solvent in the electrolyte mixture, ranging from about 1 vol% to about 30 vol%, as a fraction of all solvents in the electrolyte. At such high capacity loadings, Li salt concentrations of 1 M to 1.1 M or lower may lead to faster degradation in some designs, particularly when using high-capacity Si-containing composite anodes.

[0060] Figure 5 The effect of salt concentration on the performance of battery cells with low and high electrode capacity loadings was illustrated. These cells comprised a powder-based high-capacity, Si-containing nanocomposite anode and a powder-based intercalated cathode (lithium cobalt oxide, LCO in this example), and were cycled over a voltage range of 2.5 V to 4.4 V. Cycling stability was investigated in several exemplary cells cycled at a “C / 2” rate. Two nearly identical cells were constructed and their consistency tested. In these examples, all electrolytes contained 1 M or 1.2 M LiPF6 salt, 20 vol% FEC, 78 vol% DEC, and 2 vol% VC. Figure 5 The results shown demonstrate that a high capacity loading (5.7 mg / cm³ in this example) is achieved when the LiPF6 salt concentration increases from 1 M to 1.2 M. 2 The poor cycle stability of the battery cell with a high-quality (capacity) negative electrode can be significantly improved. At lower mass (capacity) loads (2 mg / cm³ in this example), the cycle stability can be significantly improved. 2 The positive effects of higher salt concentrations were significantly smaller (e.g., in...). Figure 5 In the comparison of 1.2M, LiPF6, and 2mg / cm³ 2 With 1.2M, LiPF6, 5.7mg / cm 2 (The curve).

[0061] In some designs, it may be advantageous to have a total salt concentration in the electrolyte ranging from about 0.8 M to about 2.0 M, while using a small fraction of fluorinated cyclic carbonates (e.g., fluoroethylene carbonate (FEC)) as a co-solvent (e.g., in the range of about 1 vol% to about 30 vol%, as a fraction of all solvents in the electrolyte), and other (e.g., fluorine-free) cyclic carbonates and linear (e.g., fluorine- or fluorine-free) carbonates with melting points ranging from about -10 °C to about -60 °C. It may be advantageous for the carbonate (e.g., cyclic carbonate) to contain a double oxygen bond (=O, carbonyl) in its molecular structure. It may also be advantageous for the carbonate (e.g., cyclic carbonate) to contain at least one methyl side group (-CH3) in its structure. In some designs, it may also be advantageous to use propylene carbonate (PC) with a melting point of about -49 °C as at least one cyclic carbonate in the electrolyte mixture. The amount of PC may preferably be in the range of about 0 vol% to about 50 vol%. In some designs, an amount of PC ranging from about 25 vol% to about 50 vol% may be advantageous. This contrasts with battery cells containing conventional graphite anodes, which typically exhibit significantly reduced stability when the PC amount exceeds 5 vol% to 20 vol%. It may also be advantageous for the electrolyte to contain a mixture of two to five cyclic carbonates with different melting points, in addition to FEC or a mixture of FEC and PC. It may be further advantageous for the electrolyte solvent to contain a mixture of LMP and RMP solvents and (optionally) ADD solvent. In some designs, it may also be advantageous for the LMP solvent or solvent mixture to contain one or more esters. In some designs, it may be advantageous for the ADD solvent to contain a small amount (e.g., about 0.1 vol% to about 5 vol%) of vinylene carbonate (VC) or vinyl ethylene carbonate (VEC) cyclic carbonates (VC may be preferred in some designs). It may be further advantageous for the total amount of all cyclic solvents in the electrolyte mixture to be in the range of about 10 vol% to about 60 vol%. It may be further advantageous that the total amount of cyclic carbonates in the electrolyte mixture is in the range of about 10 vol% to about 50 vol%. Higher amounts of cyclic solvents are generally detrimental to capacity retention at high cycling C-rates or performance at low temperatures, and in some cases, even to cycling stability.

[0062] In some designs, it may be advantageous to have a total salt concentration in the electrolyte ranging from about 0.8 M to about 2.0 M, while using a small fraction of fluoroethylene carbonate (FEC) co-solvent (e.g., ranging from about 1 vol% to about 30 vol% as a fraction of all solvents in the electrolyte), a certain amount of non-FEC cyclic carbonate (e.g., ranging from about 5 vol% to about 30 vol% as a fraction of all solvents in the electrolyte), and a certain amount of LMP co-solvent (e.g., ranging from about 20 vol% to about 70 vol% as a volume fraction of all solvents in the electrolyte). In some designs, it may be advantageous to have the electrolyte composition additionally contain at least one linear solvent (e.g., as a component of an LMP or RMP solvent or solvent mixture). In some designs, it may be advantageous to have the electrolyte composition contain at least one linear carbonate (e.g., as a component of an RMP solvent mixture). In some designs, it may be advantageous to have the electrolyte contain a mixture of two or more linear carbonates. In some designs, it may be advantageous that the fraction of (one or more) linear carbonates is from about 5% to about 60% by volume (as a volume fraction of all solvents in the electrolyte). In some designs, it may be even more advantageous that the total fraction of all (one or more) linear carbonates is from about 10% to about 30% by volume (as a volume fraction of all solvents in the electrolyte). In some designs, it may be preferred that the melting point of at least one linear carbonate, or only linear carbonate, or a mixture of all linear carbonates in the electrolyte is from about -10°C to about -60°C. In one instance, the size of the linear carbonate molecules may play an important role in the battery cell performance. For example, shorter-chain linear carbonates in the electrolyte can lead to better rate performance and, in some cases, better cycle stability. However, linear carbonates that are too short may also lead to reduced cycle stability. In some designs, the average number of atoms of the linear carbonates in the electrolyte may preferably be in the range of about 12 to about 26 per carbonate molecule. In some designs, it may be advantageous to include diethyl carbonate (DEC) as a component of a straight-chain carbonate or a mixture of straight-chain carbonates in the electrolyte. Electrolytes containing DEC can exhibit better rate performance (e.g., better capacity retention at higher rates). Furthermore, electrolytes containing DEC can provide high cycling stability in certain applications.

[0063] Figure 6The effect of exemplary electrolyte compositions on battery cell performance is illustrated. The battery cell comprises a powder-based high-capacity, Si-containing nanocomposite negative electrode and a powder-based intercalated positive electrode (lithium cobalt oxide, LCO in this example), and is cycled over a voltage range of 2.5V to 4.4V. Cycle stability was investigated in several exemplary battery cells cycled at “C / 2” rates at 45°C. Two to three (2 to 3) nearly identical battery cells were constructed, and the consistency of each electrolyte composition was tested. Electrolyte B ( Figure 6 The upper curve in the figure contains 1M LiPF6, 0.2M LiFSI, 20 vol% PC, 10 vol% FEC, 20 vol% linear carbonate (DEC in this example), 2 vol% VC, and 48 vol% linear ester (MB). Electrolyte A ( Figure 6 The lower curve in the figure contains 1.2 M LiPF6, no LiFSI, 20 vol% FEC and the same straight-chain ester (MB), and shows reduced cycling stability.

[0064] In some designs, it may be advantageous for the LMP solvent in a suitable electrolyte composition to exhibit a specific molecular size for optimal performance. The optimal size or size distribution of LMP molecules can depend on electrode characteristics (e.g., thickness, amount of binder, density, composition and capacity of the negative and positive electrodes, etc.), the electrolyte solvent mixture used, and the battery cell cycling mode (temperature, voltage range, etc.). In one example, the average LMP molecule (e.g., in an LMP solvent mixture if more than one LMP solvent is used; or in a single-solvent LMP composition) may preferably contain about 9 to about 30 atoms per solvent molecule. In some designs, it may also be advantageous for the average LMP molecule (e.g., in an LMP solvent mixture or a single-solvent LMP composition) to contain about 3 to about 10 carbon atoms in its molecular structure. Smaller LMP molecules (especially smaller linear molecules) may lead to reduced cycle stability of the battery cell. Larger LMP molecules (especially larger linear molecules) may lead to an undesirable reduction in the rate performance of the battery cell. If a straight-chain ester is used as a component of one or more LMP solvents, it may be advantageous that such esters contain an average of about 3 to about 9 carbon atoms per molecule. If one or more LMP solvents contain esters with branched chains (additional functional groups), it may be advantageous that such esters contain an average of about 4 to about 12 carbon atoms per molecule. In some designs, ester molecules with an average of 4 to 7 carbon atoms per molecule (in an LMP co-solvent) provide the most stable performance in the battery cell. In some designs, ester molecules with an average of 5 to 6 carbon atoms per molecule (in some designs, 5 carbon atoms per molecule) (in an LMP co-solvent) provide the most stable performance in the battery cell. In some designs, it may be advantageous that about 50% by volume or more of the LMP solvent contains ester molecules with an average of 5 carbon atoms per molecule.

[0065] Figures 7A to 7CThe effects of other exemplary electrolyte compositions on battery cell performance are illustrated. These cells comprise a powder-based high-capacity, Si-containing nanocomposite anode and a powder-based intercalation cathode (lithium cobalt oxide, LCO in this example), and cycle over a voltage range of 2.5V to 4.4V. Cycling stability was investigated in several exemplary cells cycled at “C / 2” rates at room temperature and 45°C. Two to three (2 to 3) nearly identical battery cells were constructed, and their consistency was tested. In these examples, all electrolytes comprised 1.2M LiPF6, 20 vol% FEC, 20 vol% linear carbonate, 2 vol% cyclic carbonate (VC in this example) as an ADD solvent, and 48 vol% linear ester. As shown in each figure, esters of different molecular sizes (and molecular weights) were selected for each electrolyte. In this illustrative example, only one type of ester (not a mixture of esters) was used in each electrolyte composition. The rate performance of the battery cells with this range of electrolytes was closely related to the carbon chain length of the esters. Battery cells using electrolytes with the shortest carbon chain length in esters exhibit the best capacity retention at higher rates, while those using electrolytes with the longest carbon chain length in esters exhibit the lowest capacity retention. In this example, esters with 6 or more carbon atoms in the molecule exhibit undesirable performance degradation. Electrolytes containing esters with 5 to 6 carbon atoms per molecule exhibit the best cycle stability at room temperature. Electrolytes containing esters with 3 carbon atoms per molecule exhibit very rapid degradation at both room temperature and 45°C. Electrolytes containing esters with 8 to 9 carbon atoms per molecule exhibit significantly faster degradation at room temperature and even faster degradation at 45°C.

[0066] In some designs where one or more esters are used as co-solvents in a suitable electrolyte mixture (e.g., for some battery cells with high-capacity nanostructured anodes and high-voltage intercalation cathodes), it may be advantageous for the total ester fraction in the electrolyte solvent to be in the range of about 20 vol% to about 70 vol% (about 30 vol% to about 60 vol% in some designs containing only straight-chain esters), as the total volume fraction of all solvents in the electrolyte. Both lower and higher ester fractions can lead to a significant decrease in cycle stability, especially at high temperatures.

[0067] In some designs, it may be advantageous (to improve battery cell performance) to use a combination of two, three, or more esters with the same chemical formula but different molecular structures in the electrolyte solvent mixture. For example, methyl butyrate (C5H4O3) could be used. 10 O2) and ethyl propionate (C5H) 10 O2) or propyl acetate (C5H) 10 O2) or butyl formate (C5H) 10O2) combinations, or multiple mixtures (or combinations thereof). Alternatively, in another instance, combinations of two, three, or more of the following esters may be used: methyl valerate (C6H) 12 O2), ethyl butyrate (C6H) 12 O2), propyl propionate (C6H) 12 O2), butyl acetate (C6H) 12 O2) and amyl formate (C6H) 12 O2). Or, in yet another instance, a combination of two, three, or more of the following esters is used: methyl hexanoate (C7H... 14 O2), ethyl valerate (C7H) 14 O2), propyl butyrate (C7H) 14 O2), butyl propionate (C7H) 14 O2), amyl acetate (C7H) 14 O2), hexyl formate (C7H) 14 O2).

[0068] In some designs, it may be advantageous (for improving battery cell performance, such as rate capability or stability) to use a combination of two, three, or more esters with similar chemical formulas in the electrolyte (e.g., those differing by no more than three carbon atoms; e.g., using esters with the chemical formula C5H). 10 O2, C6H 12 O2 and C7H 14 (A combination of esters of O2) (or, in some designs, a combination of ethers or anhydrides). In some designs, it may be advantageous if such a combination of esters (or ethers or anhydrides) exhibits a lower melting point than each individual solvent (e.g., a single ester or a single ether or a single anhydride).

[0069] In some designs, it may be advantageous (for improving battery cell performance) to use a combination of esters with or without functional groups in the electrolyte (in some designs, a combination of ethers or anhydrides). In some designs, it may be advantageous for such esters (or ethers) to have identical or similar linear (or cyclic) portions so that the presence of (e.g., different) functional groups can separate these esters (or ethers).

[0070] In some designs, when using a combination of linear and cyclic esters (and in some designs a combination of esters and ethers) and when they have functional groups, it may be advantageous (for improving battery cell performance) for at least some of the esters or ethers to remain unfunctionalized.

[0071] In some designs, it may be advantageous to use a combination of linear and cyclic esters in the electrolyte (to improve battery cell performance).

[0072] In some designs, when using a combination of linear and cyclic esters and when at least some of them have functional groups, it may be advantageous (for improving battery cell performance) for at least some of the linear and cyclic esters to have the same functional groups.

[0073] In some designs (when using a mixture of multiple esters), it may be advantageous for the straight-chain esters in the electrolyte mixture to exhibit the same chemical tail (the same R group) or belong to the same subclass.

[0074] In some designs, it may be advantageous to use a combination of ethers and esters in the electrolyte (to improve battery cell performance). In some designs, it may be advantageous to have no more than five carbon atoms in the ester molecule than in the ether molecule (e.g., the ether molecule has two or three carbon atoms, while the ester molecule has five, six, or seven carbon atoms).

[0075] In some designs, it may be advantageous to use a combination of esters, ethers and anhydrides in the electrolyte (with or without functional groups) to improve battery cell performance.

[0076] In some designs, when using combinations of esters, ethers, and anhydrides, it may be advantageous to have the same or similar straight-chain (or cyclic) portions of such esters (or ethers or anhydrides) so that the presence of (e.g., different) functional groups can separate these esters (or ethers or anhydrides).

[0077] In some designs, it may be advantageous to use a combination of linear and cyclic anhydrides in the electrolyte (to improve battery cell performance).

[0078] In some designs (e.g., battery cells with high-voltage positive electrodes), it may be advantageous (for improving battery cell performance) to use sulfones as a component of the RMP solvent. In some designs, it may be advantageous for sulfones to account for approximately 17% to approximately 97% by volume of all RMP solvents in the electrolyte formulation. In some designs, it may be advantageous for sulfones to include both cyclic and linear (or more generally, acyclic) sulfones.

[0079] The exemplary nanocomposite particles described above (e.g., negative or positive electrode particles) can typically be of any shape (e.g., near-spherical, cylindrical, plate-like, with random shapes, etc.) and any size. The maximum particle size can depend on rate performance requirements, the rate of ion diffusion into the partially filled particles, and / or other parameters. However, for most applications, the average diffusion distance from the solid-electrolyte phase interface (e.g., from the surface of the composite particle) to the core of the composite particle can be less than 10 micrometers to achieve optimal performance.

[0080] Some aspects of this disclosure are also applicable to conventional intercalation electrodes and offer benefits such as improved rate performance or improved stability, particularly for medium and high capacity loads (e.g., greater than 3 mAh / cm³). 2 ) electrodes.

[0081] In one instance, the “size” of nanocomposite particles can be determined in any of a variety of ways. In one instance, if the particles are spherical or nearly spherical, the size of a single particle can refer to the diameter of the particle. In another instance, if the particles are non-spherical (e.g., spherically similar, rectangular, etc.), the size of a single particle can refer to the diameter of an equivalent volume sphere of the particle (e.g., a representative sphere of particles of the same volume size). If the equivalent volume sphere method is used, the total pore volume from the particles is retained within the equivalent volume sphere of the particles. In yet another instance, for irregularly shaped particles (e.g., rectangular particles), the size of a single particle can refer to the minimum dimension of the particle (e.g., width) or the length of the particle (e.g., length). Thus, the various particle size ranges described with respect to embodiments of this disclosure can refer to sizes determined based on the shape and / or other characteristics of the respective particles according to any of the above methods.

[0082] This description is provided to enable any person skilled in the art to make or use embodiments of the invention. However, it should be understood that the invention is not limited to the specific formulations, process steps, and materials disclosed herein, as various modifications to these embodiments will be apparent to those skilled in the art. That is, the general principles defined herein can be applied to other embodiments without departing from the spirit or scope of the invention.

Claims

1. A lithium-ion battery cell, comprising: A porous negative electrode having a capacity loading of 2 mAh / cm³. 2 Up to 10mAh / cm 2 Within the range of [specific range], and the negative electrode comprises silicon-carbon (Si-C) composite particles having an average particle size in the range of about 0.2 micrometers to about 20 micrometers. Wherein: the total open porosity of the porous negative electrode varies from 5% to 35% by volume; A porous positive electrode, the positive electrode comprising an intercalation material comprising nickel (Ni) and / or cobalt (Co); A diaphragm electrically separates the porous negative electrode from the porous positive electrode; and An electrolyte that ion-couples the porous negative electrode to the porous positive electrode, the electrolyte comprising a composition of two or more lithium-ion salts and a solvent, the solvent composition comprising: One or more low-melting-point solvents, each of which has (1) a melting point between at least -140°C and less than -60°C and (2) a boiling point exceeding +70°C, and each of which is in the range of 10 vol% to 80 vol% of the solvent composition. One or more conventional melting point solvents, each of which has a melting point in the range of -60°C to +30°C, and each of which comprises between 20% and 90% by volume of the solvent composition. One or more nitrile additives, wherein the one or more nitrile additives are present in the solvent composition at less than 5% by volume. Wherein, the one or more low-melting-point solvents include one or more esters, and The one or more esters are in the range of 20% to 70% by volume in the solvent composition.

2. The lithium-ion battery cell according to claim 1, wherein, The one or more esters include straight-chain esters, cyclic esters, and / or esters with side branches.

3. The lithium-ion battery cell according to claim 2, wherein, The one or more esters include straight-chain esters, and the straight-chain ester is ethyl propionate.

4. The lithium-ion battery cell according to claim 1, wherein, Each of the one or more low-melting-point solvents has a boiling point exceeding +80°C.

5. The lithium-ion battery cell according to claim 1, wherein, Each of the one or more low-melting-point solvents has a melting point of at least -110°C and less than -70°C.

6. The lithium-ion battery cell according to claim 1, wherein, The one or more conventional melting point solvents include fluorinated cyclic carbonates.

7. The lithium-ion battery cell according to claim 6, wherein, The fluorinated cyclic carbonate is fluoroethylene carbonate (FEC), and the volume fraction of the FEC in the solvent composition is between 1 vol% and 30 vol%.

8. The lithium-ion battery cell according to claim 7, wherein, The solvent composition comprises ethylene carbonate (EC).

9. The lithium-ion battery cell according to claim 1, wherein, The one or more conventional melting point solvents contain at least one non-fluorinated cyclic carbonate.

10. The lithium-ion battery cell according to claim 9, wherein, The at least one non-fluorinated cyclic carbonate is vinylene carbonate (VC) and / or propylene carbonate (PC).

11. The lithium-ion battery cell according to claim 10, wherein, The one or more conventional melting point solvents contain at least one linear carbonate.

12. The lithium-ion battery cell according to claim 11, wherein, The at least one linear carbonate is diethyl carbonate (DEC).

13. The lithium-ion battery cell according to claim 1, wherein, The one or more nitrile additives include dinitrile.

14. The lithium-ion battery cell according to claim 1, wherein, The Si-C composite particles have a specific surface area in the range of about 0.5 m² / g to about 50 m² / g.

15. The lithium-ion battery cell according to claim 1, wherein, The amount of binder in the porous negative electrode ranges from about 0.5% by weight to about 14% by weight.

16. The lithium-ion battery cell according to claim 1, wherein, The total salt concentration in the electrolyte is in the range of about 1.2 M to about 1.8 M.

17. The lithium-ion battery cell according to claim 1, wherein, The two or more lithium-ion salts include LiPF6 or LiFSI.

18. The lithium-ion battery cell according to claim 17, wherein, The molar ratio of LiPF6 to LiFSI is in the range of 100:1 to 1:

1.

19. The lithium-ion battery cell according to claim 1, wherein, The embedded material comprises lithium cobalt oxide (LCO).

20. The lithium-ion battery cell according to claim 1, wherein, The porous cathode exhibits performance relative to Li / Li + 4.2V to relative to Li / Li + It exhibits the highest charging potential within the 5.1V range.

21. The lithium-ion battery cell according to claim 1, wherein, The capacity load is 4mAh / cm³. 2 Up to 10mAh / cm 2 Within the range.